Pengaruh Komunikasi Internal Dan Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan Pada PT Telkom Indonesia Tbk Di Wilayah Jakarta Selatan - Maulida Saufa Virjinia; Reni Hindriari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - This study aims to determine the Influence of Internal Communication and Transformational Leadership Style on Employee Performance at PT Telkom Indonesia Tbk in South Jakarta Area partially and simultaneously. This study uses an associative method with a quantitative approach with 104 respondents. Data analysis techniques: validity test, reliability test, classical assumption test, regression equation, correlation coefficient of determination, and hypothesis test with SPSS Version 26 software. The results of the study indicate that: (1) Internal Communication affects Employee Performance with a regression equation of Y = 4.054 + 0.843 X1. The correlation coefficient value is 0.841. The determination coefficient value of 0.707 has a significant effect on Employee Performance with the results of t count (15.698) > t table (1.984) with a significance value of 5% meaning H0 is rejected and H1 is accepted (2) Transformational Leadership Style affects Employee Performance with a regression equation of Y = 6.138 + 0.801X2. The correlation coefficient value is 0.867. The determination coefficient value is 0.751 with the calculated t result (17.556) > t table (1.984) significance value of 5% means H0 is rejected and H2 is accepted (3) Internal Communication and Transformational Leadership Style have an effect on Employee Performance regression value Y = 3.644 + 0.341X1 + 0.523X2. The correlation coefficient value is 0.881. The determination coefficient value is 0.776 Has a significant effect on Employee Performance F calculated result (175.172) > F table (3.09), with a significance of 5%, meaning Ha is accepted.